Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Asupan Cairan pada Pasien Gagal Ginjal Kronik dengan Hemodialisis di RSUD Prof. Dr. Margono Soekarjo Purwokert - Kamaluddin, Ridlwan; Rahayu, Eva (Jurnal Keperawatan Soedirman, 2009)
Chronic Renal Failure (CRF) patient who had routine Haemodialisis (HD) usually experiencing the over volume extracellular fluid because degradation of kidney`s ability to excreting fluid. Patient obidience to intake less fluid is the top priority for Nursing diagnosis on HD nurse to give the best medical servise. dominant factor that influencing patien`s obedience is not positively understandable yet. It might influenced by any other factors. The aim of this study is to analyze influencing patient compliance factors toward fluid intake for chronic renal failure patients who undergo hemodialisis at Margono Soekardjo Hospital of Purwokerto Analytic descriptive with cross-sectional design was used in this study. Data collected by closed ended questioners to the target subjects (routine HD patient) at RSUD Prof. Dr. Margono Soekarjo Purwokerto on September-October 2008.The result show that age, length of hemodialisis, education, nurses involvement, family patient involvement, self concept, knowledge level have significant level at, p= 0,100, 0,074, 0,000, , 0,000, 0,000, 0,016 and 0.001 respectively. There are five factors (education, nurses involvement, family patient involvement, and knowledge level) that have significant factor toward fluid intake. Meanwhile, two factors have no significant factor toward fluid intake as age, and length of f hemodialisis